2008
DOI: 10.1111/j.1540-8183.2008.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in Patients Treated with Heparin, Combination Antiplatelet Therapy, and Intra‐Aortic Balloon Pump Counterpulsation

Abstract: IABP-associated thrombocytopenia occurred in 57.9% of this cohort. HIT was diagnosed in 2.8% and should be considered as a diagnosis if platelet counts do not stabilize or continue to fall after 3-4 days of counterpulsation. Increased use of antiplatelet therapy does not impact the degree of thrombocytopenia although the current practice of prompt IABP removal may offset this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…1,10 As in the study by Bream-Rouwenhorst et al, we found that the degree of platelet count reduction was greater among patients with HIT than among those without HIT. 1 Because of the important clinical implications of this diagnosis, this finding suggests that IABP patients who are receiving heparin and who have a marked reduction in platelet count (>50%) should be considered for HIT testing.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…1,10 As in the study by Bream-Rouwenhorst et al, we found that the degree of platelet count reduction was greater among patients with HIT than among those without HIT. 1 Because of the important clinical implications of this diagnosis, this finding suggests that IABP patients who are receiving heparin and who have a marked reduction in platelet count (>50%) should be considered for HIT testing.…”
Section: Discussionsupporting
confidence: 75%
“…Further, on multivariate modeling, heparin use was not an independent predictor of thrombocytopenia. In conjunction with previous data demonstrating that the reduction in platelet count among patients undergoing IABP is independent of the use of clopidogrel and glycoprotein IIb/IIIa inhibitors, 1 it becomes clear that this phenomenon is largely a result of the mechanical effects of IABP.…”
Section: Discussionmentioning
confidence: 57%
“…In a study of 109 patients, 59 47% of patients with IABPs developed thrombocytopenia compared to 12% of patients not on IABPs. In a contemporary retrospective cohort study of 107 patients who had an IABP, 60 the incidence of thrombocytopenia was 57.9%. In both studies, platelet counts fell steadily until the third or the fourth day of IABP use and then stabilized.…”
mentioning
confidence: 99%
“…More than 4 hours of pretreatment with heparin has been shown to be independently predictive of post‐PCI thrombocytopenia 3 . Similarly, the occurrence and severity of IABP‐related thrombocytopenia is dependent on the duration of IABP use 60 …”
mentioning
confidence: 99%
“…Based on the fundamental in vitro and in vivo experiments, antiplatelet drugs might prevent the occurrence of HIT [38], [39]; by contrast, several clinical trials have confirmed that antiplatelet drugs do not effectively suppress the occurrence of HIT [40], and antiplatelet drugs do not reduce the occurrence and degree of thrombocytopenia [41]. However, these studies were limited to case reports or research using a small sample size.…”
Section: Discussionmentioning
confidence: 99%